Public libraries in cyberspace an evaluation of public library web sites. - Song, Sebastian Siak Shing. (2008)
The Internet Age witnessed organizations, both profit and non-profit oriented, demonstrating their eagerness to establish an online presence. The writer, as a librarian, is interested in exploring how far public libraries have ventured in cyberspace and whether they are ready to become the lighthouses in the rough seas of data. A set of 23 features from five categories, namely, Clicks-and-Mortar, Collection and Services, Design and Layout, Interactive Features, and User Education, was formulated and used to evaluate 64 public library Web sites from around the world. These Web sites from Australia, Singapore, Hong Kong, Canada, the United Kingdom, the United States, New Zealand, Norway, Finland, Iceland, Germany, France and Sweden served as proof of the level of diversity existing in the Internet environment.